Investigating the Correlation Between Tesla Stock Prices and Cryptocurrency Prices Using Pearson and Spearman Correlation Analysis (2010-2024) - Iqbal, Muhammad; Efendi, Syahril (Journal of Digital Market and Digital Currency, 2025)
This study investigates the correlation between Tesla's stock prices and the prices of the two leading cryptocurrencies, Bitcoin and Ethereum, from 2010 to 2024. By employing both Pearson and Spearman correlation analyses, the research identifies strong positive correlations between these assets, with Tesla-Bitcoin showing a Pearson coefficient of 0.76 and Tesla-Ethereum at 0.82. The Spearman correlations further validate these findings, indicating that Tesla's stock prices are significantly aligned with the movements of Bitcoin and Ethereum. The results suggest that similar market forces and investor sentiments influence both Tesla and these cryptocurrencies. This strong correlation implies that investors should be cautious when seeking diversification, as these assets tend to move together, potentially amplifying portfolio risk. The study's findings underscore the importance of considering cross-market dynamics in investment strategies and highlight the interconnectedness of traditional and digital financial markets. Future research could explore the relationships between other technology stocks and digital assets, as well as the evolving correlations in response to major market events.